Musibah dalam Perspektif Al-Qur’an - Muhammad Ikhsan; Azwar Iskandar (Studia Quranika, 2022)
This study aims to explain: (i) how the nature of calamity in the Qur'an; (ii) what is the attitude of mankind towards calamity according to the Qur'an; and (iii) how to deal with calamity according to the Qur'an. This study uses the mawdu'i (thematic) method with a qualitative descriptive approach. The results showed that: (i) the calamity in the Qur'an with all its derivations boils down to an unexpected event and can mean positive or negative; (ii) According to the Qur'an, in general, the attitude of man is facing and responding to calamity determined by God there are two attitudes: (1) the attitude of the man that is only in accordance with his own personal desires, and (2) the attitude of the praiseworthy man, namely al-Mukhbitun. This last attitude is the characteristic of a true believer who gets good news from God; (iii) the solution to the calamity according to the Qur'an is inferred on the awareness to immediately return to God through repentance for all sins that can invite calamity and hasten to do righteous deeds, and be patient and rely on Allah.